The external trade of the CACM-countries - Bernhard Klinner (Intereconomics, 1974)
The Central-American Common Market (Mercado Común Centroamericano — MCC) was established in 1960 and its members are: Costa Rica, EI Salvador, Guatemala, Honduras and Nicaragua. Purpose of this article is meant to be a reflection on these countries' development of their external trade during the period 1960–1972.
Keywords: 330; Trade